Daylight sensor switch using light sensor controlled by LM7809IC - Abdul Rahim, Muhammad Faiz; Mad Siam, Muhammad Naqib (2016)
This project is mainly based on LDR that actuate based on light for switching purposes. There is a load connected at the end of the LDR-switch circuit where it controls 2 motor. The motors will be applied to a curtain to make an automated curtain that is controlled by the LDR.